Investigating a new alarming outbreak of flavescence dorée in Tuscany (Central Italy): molecular characterization and map gene typing elucidate the complex phytoplasma ecology in the vineyard agroecosystem - Pedrelli, Athos; Carli, Marco; Panattoni, Alessandra; Pellegrini, Elisa; Rizzo, Domenico; Nali, Cristina; Cotrozzi, Lorenzo (Frontiers in Plant Science, 2024)
Flavescence dorée (FD) is a major disease for grapevine in Europe, despite the quarantine status of its causal agent (FD phytoplasma, FDp) and the mandatory monitoring and vector control practices.As alarming FD epidemic outbreaks continue to appear in Tuscany (Central Italy), a four-year survey was carried out in the main wine-growing areas of the region, where the FD presence was investigated in both primary and secondary FDp hosts and vectors, i.e., Vitis vinifera (VV), Clematis vitalba (CV), Alnus glutinosa (AG), Scaphoideus titanus (ST) and Dictyophara europaea (DE). This work (i) confirmed the FD diffusion in almost the whole Tuscany, and even with an increased occurrence rate (around 50% of samples tested positive); (ii) highlighted a complex FDp ecology also in Tuscany vineyard agro-ecosystems, as FDp was reported not only in VV and ST, but also in secondary vectors (DE) and hosts (AG and CV); (iii) reported nine FDp strains (three of which were novel), belonging to all the three methionine aminopeptidase (map)-clusters, i.e., map-FD1, -FD2 and -FD3, with the map-FD3/M51 genotype mostly reported in VV, but also in DE and CV; and (iv) further confirmed a complex FDp ecology in the vineyard agro-ecosystem, also by phylogenetic analyses carried out at both Italian and European levels, which also showed some relations between the Tuscany FDp strains and those reported in the Balkans and the French scenario. We believe that the outcomes here reported will be useful to prevent and control the spread of the harmful FD.